2022
DOI: 10.3390/ijerph191610262
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Post-Exposure Evaluation (COPE) Study: Assessing the Role of Socio-Economic Factors in Household SARS-CoV-2 Transmission within Campania Region (Southern Italy)

Abstract: Campania is the sixth poorest region of Italy, and it is the region with the highest income inequality. The secondary attack rates of SARS-CoV-2 among households are found to be substantially heterogeneous among published studies and are influenced by socio-economic factors. We conducted a retrospective study to describe the role of socio-economic factors in the household transmission of SARS-CoV-2 among patients living in Campania Region and referring to “Federico II” Hospital. We interviewed 413 subjects fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Disparities across the social ladder of the society concerning COVID-19 have been shown to concern mainly the access to test 53 – 55 , and the COVID-19 mortality and morbidity 56 , 57 . Even if the dependence of SAR on some socio-economic variables have been shown in small samples in some countries 58 , 59 , it may be dependent on a particular situation or time.…”
Section: Discussionmentioning
confidence: 98%
“…Disparities across the social ladder of the society concerning COVID-19 have been shown to concern mainly the access to test 53 – 55 , and the COVID-19 mortality and morbidity 56 , 57 . Even if the dependence of SAR on some socio-economic variables have been shown in small samples in some countries 58 , 59 , it may be dependent on a particular situation or time.…”
Section: Discussionmentioning
confidence: 98%
“…Disparities across the social ladder of the society concerning COVID-19 have been shown to concern mainly the access to test 36,60,61 , and the COVID-19 mortality and morbidity 62,63 . Even if dependence of SAR on some socio-economic variables have been shown in small samples in some countries 64,65 , it may be dependent on a particular situation or time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even if sick individuals use masks or isolate from household members, pre-symptomatic or asymptomatic individuals may still transmit infection. Multiple studies from all over the world have shown high SARS-CoV-2 household secondary attack rates and how socio-economic factors can affect viral transmission within the household [26][27][28][29][30][31][32]. Notably, as this study was conducted in the fall of 2020, a significant number of participants were probably infected during the first wave of the pandemic (March to July 2020), when COVID-19 incidence was much higher among Hispanics than in other ethnic groups in NC [11].…”
Section: Discussionmentioning
confidence: 99%